Social-emotional learning in a week-long theatre camp for youth - Emily E. Virtue; Lisa C. Mann; Hannah Diener (Current Issues in Middle Level Education, 2025)
Understanding how social-emotional learning develops in middle level education is important for educators and parents as they work to guide youth toward healthy relationships and responsible citizenship. Many studies demonstrate that students who participate in theatre have shown greater emotional health and more capacity to move through conflict positively. This study asks if social-emotional learning through theatre education can still happen outside of a formal educational setting. This study is a mixed methods investigation of a week-long theatre camp in the summer for upper elementary and middle school youth. Four aspects of social emotional learning were studied: task articulation, self-regulation, peer relationships and confidence. The findings demonstrated relationships between the four aspects of social emotional learning studied and suggest that social-emotional learning may not need to be formal to be impactful for students’ development.